Foot-and-mouth disease in tropical wildlife - Pinto, A. A. (New York Acad Sciences, 2004)
This review of foot-and-mouth disease in cloven-hoofed, free-living animals, describes the disease, the wide range of the hosts, the carrier state, and the interrelationship between disease in domestic livestock and wildlife. This information becomes even more crucial to the development of control strategies when linked to the process of pathogenesis and the epidemiology of the disease.
Keywords: foot-and-mouth disease; tropical wildlife; epidemiology; trade in animals